The Okhotsk-Japan Circulation Pattern and the Heavy Rainfall in Beijing in 2012 Summer - Yafei Wang; Jianzhao Qin; Lijuan Zhu (Advances in Meteorology)
Using station precipitation and reanalysis data, we examined the evolution of the large-scale circulations associated with the heavy rainfall event that occurred around July 21, 2012 (721 heavy rainfall). This study focuses on a role that the large-scale circulations named “the Okhotsk-Japan (OKJ) circulation pattern” played in causing the heavy rainfall case. We found that the 721 heavy rainfall occurred under a background of the OKJ circulation that persisted for about 10 days. However, the pattern was different from the normal OKJ circulation, for this circulation pattern accompanied a blocking high between the Ural Mountains and the Baikal Lake. This difference resulted from the seasonal change of the basic flow. The related Rossby wave propagated eastward during the persisting period of the dominated OKJ pattern. This caused the development of a low-pressure system around the Baikal Lake and the weakening of a ridge around the Okhotsk Sea. The slow evolution of the OKJ circulation created a favorable environment for the moisture transport to northern China, assisting in the generation of the 721 heavy rainfall.